PENGARUH KONSORSIUM PBRM (PLANT BENEFICIAL RHIZOSPHERIC MICROORGANISM) DALAM NUE (NUTRIENT USE EFFICIENCY) PADA PERTUMBUHAN JAGUNG (Zea mays L.) - Tyas Nyonita Punjungsari; Agung Setya Wibowo; Intan Fuji Arriani; Palupi Puspitorini (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2019)
Corn farm processing in Blitar Regency is very dependent on fertilization using chemicals. The use of chemicals themselves has a negative impact on the environment and health if used continuously. Therefore we need a solution to increase the absorption of nutrients from the soil by plants (nutrient use efficiency), namely the use of beneficial microorganisms, namely PBRM (Plant Beneficial Rhizospheric Microorganism). The purpose of this study was to determine the effect of a consortium of soil from peanut plants in increasing the growth of corn plants. This research was conducted in May 2019 until September 2019. This study used RAK and was carried out in several stages, the first being planting corn seeds with a combination of NPK and PBRM Consortium, with each of 4 dose levels, K0, K1, K2, K3 Observation indicators consisted of plant height, leaf area, wet weight of cob, dry weight of cob. DMRT test results on the variable Plant Height that the treatment of K2 (1.5 kg Consortium per plant) showed the best results with an average of 7 DAP (9.40) 14 dd (40.96) 28 DAP (102.36) 35 DAP (141, 31) and 42 DAP (172.21) while the age of 21 DAP in the K3 treatment (3 kg consortium) with the average (74.80) which showed the best results on corn plant height. Based on analysis of variance of leaf area observations, it was shown that the administration of PBRM consortium in NUE had a significant effect on the age of 21 DAP, 28 DAP, 35 DAP, and 42 DAP but did not significantly affect the age of 14 HST. In the variable wet weights of K2 treatment cob showed the highest average of 527.33 grams while in the variable dry weight of K2 treatment cob showed the highest average of 493.63 gr.